1983
DOI: 10.1148/radiology.147.1.6828720
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nuclear magnetic resonance on patients with cardiac pacemakers.

Abstract: The effect of nuclear magnetic resonance (NMR) imaging on six representative cardiac pacemakers was studied. The results indicate that the threshold for initiating the asynchronous mode of a pacemaker is 17 gauss. Radiofrequency levels are present in an NMR unit and may confuse or possibly inhibit demand pacemakers, although sensing circuitry is normally provided with electromagnetic interference discrimination. Time-varying magnetic fields can generate pulse amplitudes and frequencies to mimic cardiac activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(27 citation statements)
references
References 0 publications
0
26
0
1
Order By: Relevance
“…The medical literature from the pre-MR conditional cardiac device era arises from: 1) in vitro investigations of cardiac pacemakers and implantable cardiac defibrillators (ICDs), 2) isolated case reports, 3) retrospective series of patients with devices unintentionally or intentionally placed in the MRI environment and 4) prospective studies with defined patient and MR conditions [4-69]. Additionally, a physician initiated prospective multicenter site registry of pacemakers and ICDs using 1.5 Tesla non-thoracic scans has been initiated (The MagnaSafe Registry) [70,71].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The medical literature from the pre-MR conditional cardiac device era arises from: 1) in vitro investigations of cardiac pacemakers and implantable cardiac defibrillators (ICDs), 2) isolated case reports, 3) retrospective series of patients with devices unintentionally or intentionally placed in the MRI environment and 4) prospective studies with defined patient and MR conditions [4-69]. Additionally, a physician initiated prospective multicenter site registry of pacemakers and ICDs using 1.5 Tesla non-thoracic scans has been initiated (The MagnaSafe Registry) [70,71].…”
Section: Introductionmentioning
confidence: 99%
“…The transfer of electromagnetic energy can lead to myocardial electrical stimulation, tissue destruction at the lead tip/endocardial interface, pain, and damage to the pulse generator circuitry/battery. This may produce adverse effects on sensing, pacing thresholds, and lead impedances, and can cause inappropriate pacing acceleration or inhibition, and battery depletion [4,6,7,9,20,29,31,33,36,41,43,50,52,61,62,98-100] In a recent investigation by Wilkoff et al [81] on an MR conditional pacing system, these adverse effects were not observed. Pacing thresholds did not change significantly between patients with the device who were scanned and those who served as control patients.…”
Section: Introductionmentioning
confidence: 99%
“…Pavlicek et al [8] were the first (1983) to discuss the potential interaction between pacing devices and the NMR (at that time nuclear magnetic resonance) environment using ex-vivo pacemakers of deceased patients. These interactions can be subdivided into three categories.…”
Section: Interaction Between the Mri System And Ciedsmentioning
confidence: 99%
“…Phantom studies have demonstrated the potential for pacemakers to move when placed within the static magnetic field of an MRI unit. 17 In reality, the magnetic force and torque generated by the static magnetic field of a 1.5 T scanner does not pose a safety concern for modern pacemakers that are smaller, contain fewer moving parts and little ferromagnetic material. Pacing leads are nowadays constructed from materials that are less magnetically susceptible (MP35N or drawn brazen strand) and as such pose little risk of movement or dislodgement.…”
Section: Reed Switch Activation and Pacemaker Displacementmentioning
confidence: 99%